Changes in the physicochemical parameters and microbial community of a new cultivar blue wheat cereal wholemeal during sourdough production - Bartkiene, Elena; Starkute, Vytaute; Zokaityte, Egle; Klupsaite, Dovile; Mockus, Ernestas; Ruzauskas, Modestas; Bartkevics, Vadims; Borisova, Anastasija; Rocha, João Miguel; Ozogul, Fatih; Liatukas, Zilvinas; Ruzgas, Vytautas (Frontiers in Microbiology, 2022)
Changes in the characteristics of a new cultivar (DS8472-5) of blue wheat during wholemeal fermentation with Pediococcus acidilactici (LUHS29), Liquorilactobacillus uvarum (LUHS245) and Lactiplantibacillus plantarum (LUHS122), including acidity, microbiological and chromaticity parameters, free amino acid (FAA), gamma-aminobutyric acid (GABA) and biogenic amine (BA) contents, macro- and micro-element concentrations and fatty acid (FA) and volatile compounds (VC), were evaluated. In addition, a metagenomic analysis was performed. The lactic acid bacteria (LAB) strains used for fermentation was a significant factor in wholemeal fermentation sample pH, redness (a*) and LAB counts (p ≤ 0.05). In most of the samples, fermentation increased the FAA content in wheat wholemeal, and the highest concentration of GABA was found in DS8472-5 LUHS122 samples. Phenylethylamine was found in all wheat wholemeal samples; however, spermidine was only detected in fermented samples and cadaverine only in DS8472-5 LUHS122. Fermented samples showed higher omega-3 and omega-6 contents and a higher number and variety of VC. Analysis of the microbial profile showed that LAB as part of the natural microbiota present in cereal grains also actively participates in fermentation processes induced by industrial bacterial cultures. Finally, all the tested LAB were suitable for DS8472-5 wheat wholemeal fermentation, and the DS8472-5 LUHS122 samples showed the lowest pH and the highest LAB viable counts (3.94, 5.80 °N and 8.92 log10 CFU/g, respectively).